Nutritional assessment of Zea mays and Oryza sativa stover for sheep feeding in the Ecuadorian Tropic - Sánchez Laiño, Adolfo Rodolfo (2015)
Bromatological chemistry (Weende), the components of the cell wall (Van Soest), and the nutritional value is determined through in vivo digestibility to estimate the value of MS and NDT, evaluate and meat production profitability by using two agricultural products (corn stover and rice), fortified with three levels of molasses and urea (1; 2 and 3%) in tropical mestizos feeding sheep. The digestibility coefficients for DM, OM, CP, CF, EE, and ELN corn stover are in the order of 40.49; 48.56; 22.14; 64.55; 67.03, and 36.94%, respectively, while for MS and NDT values 1377.80 kcal kg-1 DM and 40.39% are recorded, surpassing the rice (P <0.01). There is a high degree of positive association between FC and content CDMO (r= 0.984). The greatest CA (P<0.01), recorded the treatment based on rice stubble (1,343 kg DM animal-1  day-1). While corn stover had the highest GPD, more efficient ICA, and RC (0.132 kg animal-1 d-1, 7.50 and 45.09%). Urea levels did not affect (P>0.05) the CA, the GPD, the ICA, and the RC. Treatments based on rice stubble and corn combined with molasses and urea exceed (P<0.01) the control (free grazing). The higher return is obtained by providing the combined corn stover 2 and 3% of urea (50.15 and 34.91%, respectively). The use of agricultural waste, enriched with molasses and urea, as a staple food for tropical sheep, is an alternative food for the dry season on the Ecuadorian coast